Fogarty balloon catheter: a technical aid in the removal of tracheo-bronchial foreign bodies - Saylam, Argun; Yener, Ali; Tanrıverdi, Belkıs; Aytaç, Aydın (The Turkish Journal of Pediatrics, 1976)
Fogarty balloon catheter, originally designed for the removal of intravascular blood clots, has been found useful also in the extraction of stones in the biliary ductus, stones in the ureter, salivary calculus and blunt esophageal and tracheo-bronchial foreign bodies. Some of the blunt spheric foreign bodies like beads in the tracheobronchial tree can sometimes not be grasped by the usual bronchoscopic forceps and these patients are subjected to thoracotomy and bronchotomy for the removal of these bodies. Foreign bodies like beads have a hole in their corpus through which a Fogarty catheter can be passed and inflated beyond them. Simultaneous withdrawal of the bronchoscope and catheter results in safe removal of these kinds of foreign bodies. Such a case was presented in this paper.